2023
DOI: 10.3389/fpls.2023.1130545
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria assessment to screen climate smart rice establishment techniques in coastal rice production system of India

Abstract: IntroductionConventional rice production techniques are less economical and more vulnerable to sustainable utilization of farm resources as well as significantly contributed GHGs to atmosphere.MethodsIn order to assess the best rice production system for coastal areas, six rice production techniques were evaluated, including SRI-AWD (system of rice intensification with alternate wetting and drying (AWD)), DSR-CF (direct seeded rice with continuous flooding (CF)), DSR-AWD (direct seeded rice with AWD), TPR-CF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 123 publications
0
1
0
Order By: Relevance
“…The two studies that covered all three gases and CRC, AWD, and SRI have very different results. Rajesh Krishnan et al (2017) found CO 2 emissions to be the lowest for CRC, higher for AWD, and highest for SRI [38]; while Mohapatra et al (2023) found the opposite [61]. These results are set out in the Supplementary Materials file, but they do not support any conclusions on this point.…”
Section: Carbon Emissions and Sequestrationmentioning
confidence: 89%
“…The two studies that covered all three gases and CRC, AWD, and SRI have very different results. Rajesh Krishnan et al (2017) found CO 2 emissions to be the lowest for CRC, higher for AWD, and highest for SRI [38]; while Mohapatra et al (2023) found the opposite [61]. These results are set out in the Supplementary Materials file, but they do not support any conclusions on this point.…”
Section: Carbon Emissions and Sequestrationmentioning
confidence: 89%